Are negative parental attributions predicted by situational stress?: from a theoretical assumption toward an experimental answer - Beckerman, Marieke (Child maltreatment, 2020)
In an experimental within-subjects research design, we studied the theoretical assumption that stress predicts negative parental attributions, which until now was mainly studied using cross-sectional study designs. During home visits to 105 families, mothers and fathers were subjected to two experimental conditions and two control conditions. In the experimental conditions, parents completed the Parental Attributions of Child behavior Task (PACT, a computerized attribution task) under two different stressful conditions (i.e., cognitive load and white noise); in the control conditions, the PACT was completed without additional stressors. Furthermore, parents completed questionnaires about existing risk factors (i.e., partner-related stress, parenting stress, and abuse risk). There were no main effects of induced stress on attributions for fathers and mothers, but we found that a combination of induced situational stress (cognitive load) and high risk resulted in the most negative parental attributions in mothers. The discussion focuses on intensity and origin of stressors, comparison between mother and father attributions, implications for interventions, and possible future research directions.